2008
DOI: 10.1111/j.1365-3180.2008.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of pesticide policies and regulations for urban amenity areas in seven European countries

Abstract: Summary An analysis of the regulations of herbicide use for weed control in non‐agricultural/urban amenity areas, including actual pesticide use, was carried out as a joint survey of seven European countries: Denmark, Finland, Germany, Latvia, the Netherlands, Sweden and United Kingdom. Herbicides constitute the major part of the pesticides used in urban amenity areas. Herbicide use on hard surfaces is the largest in terms of volume and potential contamination of surface and groundwater. The aim of the study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 13 publications
0
37
0
Order By: Relevance
“…Although several herbicides are in use, glyphosate-containing herbicides (GCH) are by far the most widely used herbicide for weed control on hard surfaces [32][33][34][35]. Recent work on the impact of GCH on pollution atenuation and biodegradation in a PPS indicated that GCH is not retained in the PPS structure and is subject to rapid wash through in response to water movement thus increasing the potential risk of reaching receiving environments [36].…”
Section: Current Perspective On Irrigation and Drainagementioning
confidence: 99%
“…Although several herbicides are in use, glyphosate-containing herbicides (GCH) are by far the most widely used herbicide for weed control on hard surfaces [32][33][34][35]. Recent work on the impact of GCH on pollution atenuation and biodegradation in a PPS indicated that GCH is not retained in the PPS structure and is subject to rapid wash through in response to water movement thus increasing the potential risk of reaching receiving environments [36].…”
Section: Current Perspective On Irrigation and Drainagementioning
confidence: 99%
“…In many countries the risk of pollution of the environment has led to restrictions on pesticide use, and herbicides have been replaced by other means like flame weeding or mechanical weed control, e.g., in urban areas (Bond & Grundy, 2001;Kristoffersen et al, 2008a). These methods control a wide range of annual weed species, but plant species with protected meristems such as grass weeds and some perennial weed species pose a special problem because of their ability to regrow after treatment (Ascard, 1994(Ascard, , 1995Andreasen et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…With these results, the political interest in the environment could be considered as moderate (Kristoffersen et al, 2008). Thus, adoption of an ethical attitude will be limited until citizen support is expected.…”
Section: Progressive Pesticide Awareness Of Urban Pesticide Usementioning
confidence: 99%
“…Thus, adoption of an ethical attitude will be limited until citizen support is expected. For example, despite its legislation strictly controlling urban pesticide use since 1954, Finnish people do not show a willingness to complete its legislation by greater amenity pesticide control (Kristoffersen et al, 2008). Moreover, hard surfaces or the status of amenity areas could curb initiatives: in the United Kingdom, administrative land fragmentation results in local authorities being responsible for weed control (Grundy, 2007).…”
Section: Progressive Pesticide Awareness Of Urban Pesticide Usementioning
confidence: 99%
See 1 more Smart Citation